Hesitancy In Edith Wharton's The Age Of Innocence Novel (1920): A Psychoanalytic Approach - Putra Pramasurya, Agwiadam, Dr. Phil. Dewi Candraningrum, M.Ed, Dr. Abdillah Nugroho, M. Hum (2015)
ABSTRACT AGWIADAM PUTRA PRAMASURYA. A320110084. HESITANCY IN EDITH WHARTON's THE AGE OF INNOCENCE NOVEL (1920): A PSYCHOANALYTIC APPROACH. RESEARCH PAPER. MUHAMMADIYAH UNIVERSITY OF SURAKARTA. JUNE, 2015. This study is aimed to reveal the hesitancy in The Age of Innocence (1920) novel by Edith Wharton. The major problem of this study is hesitancy when the first time he love with his fiancée, namely is May Welland. One more time, his life changes when he meets Countess Ellen Olenska, May cousin but also have love affair with her. May offers to release him from their engagement, and he can marry the woman he truly loves. May appears to trust him, at least at first. Thus hesitancy occurs when he will engaged with May Welland, he must to settle and handle divorce cases May cousin that is Ellen. He and Mr. Letterblair will discuss divorce case between Ellen and her husband. Newland Archer feels hesitancy because he not sure can solve divorce this cases. The objective of this study is to analyze Edith Wharton's The Age of Innocence (1920) novel on the structural elements and analyze this novel based on Psychoanalytic Approach. The researcher employs descriptive qualitative research. The researcher uses two types of data sources. The source of primary data is Edith Wharton's The Age of Innocence (1920) novel. The secondary data sources are from books, biography of the author, journals, and internet sources related to the study. The two kinds of data collected through library research and the technique of data collection is descriptive analysis. Based on the research, the researcher draws the following conclusions. First, the study shows that the problem which is faced by the major character is love affair. Newland Archer feels hesitated about his love between May Welland or Ellen. Newland Archer learns she had always known of his continued love for Ellen, because he surrendered the thing most meaningful to him out of loyalty to their marriage. Second, based on psychoanalytic approach in id, ego, superego and the hesitancy of physiological the major character reflected in Edith Wharton's The Age of Innocence (1920) novel. Keywords: hesitancy, the age of innocence, psychoanalytic approach